Hematospermia: an unusual cause of urology emergency - Muhammad Hilmi Hashim,; Goh, Eng Hong; Tan, Guan Hee; Rozman Zakaria,; Nik Azuan NI,; Fam, XI; Mohd Hafidzul Jasman, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2017)
Hematospermia is a distressing disorder in sexually active men resulting in great concern to the patient. We report an unusual case of hematospermia with an atypical presentation, involving a 54-year-old man presented with acute urinary retention after sexual intercourse. Although the causes are widely known, arteriovenous malformation as the cause of this disorder has not much been reported in the literature. Transcatheter embolization of internal pudendal artery is a promising option for hematospermia caused by arterial fistula or bleeding.